2017
DOI: 10.1080/10872981.2017.1377038
|View full text |Cite
|
Sign up to set email alerts
|

Creating a medical education enterprise: leveling the playing fields of medical education vs. medical science research within core missions

Abstract: Background: Unlike publications of medical science research that are more readily rewarded, clinician-educators’ scholarly achievements are more nebulous and under-recognized. Objective:Create an education enterprise that empowers clinician-educators to engage in a broad range of scholarly activities and produce educational scholarship using strategic approaches to level the playing fields within an organization. Design: The authors analyzed the advantages and disadvantages experienced by medical science resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Specifically, research tends to be more valued than teaching. The former offers easily evaluated outcome measures such as the publication of articles and receipt of grants, and a tangible impact on remuneration [ 41 ] and academic promotion [ 42 ]. In principle, academic promotion committees recognize the importance of teaching [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research tends to be more valued than teaching. The former offers easily evaluated outcome measures such as the publication of articles and receipt of grants, and a tangible impact on remuneration [ 41 ] and academic promotion [ 42 ]. In principle, academic promotion committees recognize the importance of teaching [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Career success refers to a person's accumulated positive work‐related achievements or psychological sense of achievement (Cumbler et al, 2018 ). At present, most of the researches on career success are concentrated in the field of enterprise management, but gradually, researches have turned to the field of nursing (Brown et al, 2018 ; Thammasitboon et al, 2017 ). Researches have showed that career success is helpful to promote the innovative behaviour of nurses, and it can improve the quality of service and stabilize the nursing teams (Wang, Zhang, et al, 2019 ; Zamanzadeh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…14,19,21,25,26,29,39 Five programs were organized as formal fellowships. 17,19,21,23,43 The number of people required to administer each program was not generally reported, and Appendix 2 reports only the minimum number of personnel required. Fifteen of the programs reported needing 10 people or fewer to run.…”
Section: Program Characteristics and Participationmentioning
confidence: 99%